Impact of sisam (Dalbergia sissoo) boundary plantation on associated fodder crops in rainfed semi-arid region - GILL, A S; BURMAN, D; BAIG, M J; PRASAD, J V N S (The Indian Journal of Agricultural Sciences, 2011)
ALL expriement was conducted during 1999-2001 to study the sissoo (Dalbergia sissoo Roxb) boundary plantation on associated fodder crops sequenced \vith pearl millet  (Pennisetuln glaucum(L.) R. Br. enlcnd. Stuntz),and oat (Avena sativa L.) gro\vn under rainfed conditions in semi-arid region. The intlue.1cc oftree on the fodder crops sequence in ternlS of bionlass accumulation, plant height, leaf-area index, specific leafareJ 2nd green forage yield \vas found to be negative up to 5 n1 in north and 3 nl in south of tree and beyond that distance no significant influence was noticed. The correlation test between photosynthetically active radiation and crop gro\vth and yield indicated that the more negative influence of tree on the growth and yield of crops near to tree and at north than at south was owing to the shading oftrcc. In order to predict the perfom1ance of crops grown at different distances and directions of Dalbergia sissoo boundary plantation the best-fit  equations were developed.